Continued attendance for paediatric weight management: A multicentre, qualitative study of parents' reasons and facilitators. Issue 3 (18th February 2019) - Farnesi, Biagina‐Carla; Perez, Arnaldo; Holt, Nicholas L.; Morrison, Katherine M.; Gokiert, Rebecca; Legault, Laurent; Chanoine, Jean‐Pierre; Sharma, Arya M.; Ball, Geoff D.C.
Abstract : Although prolonged engagement in paediatric weight management (PWM) is associated with positive treatment outcomes, little is currently known about enablers of long‐term programme attendance. The purpose of our study was to explore families' reasons for and facilitators of their continued attendance at health services for PWM. Semi‐structured, individual interviews were conducted with parents of children (10‐17 year old; body mass index ≥85th percentile) who completed the active phase of treatment in one of four Canadian multidisciplinary clinics for PWM. Interview data were recorded digitally, transcribed verbatim and analysed thematically. Parents' (n = 40) reasons for continued clinic attendance included ongoing concerns (eg, parental concern about their child's health), actual and expected benefits from treatment (eg, lifestyle improvements) and perceived quality of care (eg, structured, comprehensive, tailored health services). Several logistical and motivational factors contributed to continued attendance, including flexible work schedules, flexible appointment times, financial resources and children's motivation for treatment. Helping families address treatment barriers and ensuring that weight management services meet families' treatment expectations are promising strategies to enhance retention in PWM to optimize health outcomes.